A special type of liver failure after partial hepatectomy: a case report - Gao, Linxiao; Tu, Bing; Cheng, Mingxiang; Wang, Menghao (Frontiers in Oncology, 2025)
Posthepatectomy liver failure (PHLF) is one of the most harmful complications after liver resection. Here, we report a case of a specific type of PHLF in a 60-year-old man with hepatocellular carcinoma. The patient developed extensive liver necrosis accompanied by further deterioration of liver function and coagulation on the eighth postoperative day. After being treated with liver protection, circulation improvement, plasma infusion, and anti-infective therapy, his bilirubin level still increased progressively, and renal function deteriorated with anuria. Finally, the patient’s family discontinued treatment. This case highlights the importance of the timely identification and management of this special type of PHLF.